Recent Advances in Mn‐Rich Layered Materials for Sodium‐Ion Batteries. (20th January 2023) - Wang, Kuan; Zhuo, Haoxiang; Wang, Jiantao; Poon, Fanny; Sun, Xueliang; Xiao, Biwei
Abstract: Branded with low cost and a high degree of safety, with an ambitious aim of substituting lithium‐ion batteries in many fields, sodium‐ion batteries have received fervid attention in recent years after being dormant for decades. Layered materials are a major focus of study owing to the extensive experience already gained in lithium‐ion batteries, and the pursuit of a Mn‐rich composition is critical to reduce the cost while retaining the performance. This review provides a timely update of the recent progress of Mn‐rich layered materials for sodium‐ion batteries based on the understandings of the phase forming principles, structure transformation upon cycling and charge compensation mechanisms and discusses potential ambiguities in the pursuit of high‐performance materials. Abstract : The year of 2022 has witnessed a great leap forward for the commercialization of sodium‐ion batteries (SIBs) due to the unprecedented growth of lithium price. However, the "triangle paradox" of obtaining high energy density with low cost and long cycle life simultaneously turns out to be more complicated in quest of an outstanding SIB.